From Hydrological Data to Economic Governance: Expanding the Analytical Capacity of Water Accounts - Motuzka, O.; Grod, M. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The study builds on the hypothesis that the effectiveness of water resource management directly depends on the level of analytical maturity of water accounting systems. The traditional model, focused mainly on recording the physical parameters of the water balance, does not provide an adequate foundation for the formulation of strategic economic and environmental decisions. The integration of hydrological, ecological, and economic data within a unified analytical framework transforms water accounting into a tool of economic governance, capable of measuring not only water volumes but also its value, productivity, and contribution to sustainable development. The harmonization of statistical, hydrological, and economic methods enhances the analytical capacity of water accounting, making it an effective mechanism for assessing the state of natural assets and supporting decision-making at macro- and meso-levels. The purpose of the article is to develop methodological foundations for the formation of analytical water accounts that integrate physical, economic, and institutional parameters in order to improve the effectiveness of decision-making systems in the field of water resource management. This approach reconsiders the role of water accounting as not merely a statistical but also a managerial instrument that connects physical resource flows with economic indicators of sustainability. The article outlines the main directions of integrating environmental and economic water accounting systems, identifies analytical parameters capable of ensuring coherence between natural processes and economic decisions, and substantiates their potential for supporting sustainable development policy. For the first time, a conceptual understanding of water accounting is proposed as an integrated analytical system that combines hydrological, administrative, and economic levels of observation, ensuring a transition from the registration of natural indicators to the managerial interpretation of water resources as an economic asset. As a result of the study, methodological principles have been developed for the formation of analytical water accounts that ensure a transition from a purely hydrological dimension to a comprehensive economic and managerial approach. The expediency of using the water account as an instrument for integrating physical, economic, and institutional data to support decision-making based on harmonized water indicators has been scientifically substantiated. The proposed approach advances the modern understanding of analytical water accounting, within which water is regarded not only as a natural resource but also as an economic asset that affects productivity, sustainable development, and financial stability. The scientific novelty of the results lies in the formulation of a theoretical and methodological model of analytical water accounting as a mechanism for transitioning from descriptive hydrological recording to systemic economic and managerial analysis, which further develops the concept of an integrated system of water management.